High production of recombinant protein using geminivirus-based deconstructed vectors in Nicotiana benthamiana - Kim, Nan-Sun; Lee, Kyeong-Ryeol; Lee, Jihyea; Kil, Eui-Joon; Lee, Juho; Lee, Seon-Kyeong (Frontiers in Plant Science, 2024)
We focused on the geminiviral vector systems to develop an efficient vector system for plant biotechnology. Begomoviruses and curtoviruses, which belong to the Geminiviridae family, contain an intergenic region (IR) and four genes involved in replication, including replication-associated protein (Rep, C1), transcriptional activator (TrAP, C2), and replication enhancer (REn, C3). Geminiviruses can amplify thousands of copies of viral DNA using plant DNA polymerase and viral replication-related enzymes and accumulate viral proteins at high concentrations. In this study, we optimized geminiviral DNA replicon vectors based on tomato yellow leaf curl virus (TYLCV), honeysuckle yellow vein virus (HYVV), and mild curly top virus (BMCTV) for the rapid, high-yield plant-based production of recombinant proteins. Confirmation of the optimal combination by co-delivery of each replication-related gene and each IR harboring the Pontellina plumata-derived turbo green fluorescence protein (tGFP) gene via agroinfiltration in Nicotiana benthamiana leaves resulted in efficient replicon amplification and robust protein production within 3 days. Co-expression with the p19 protein of the tomato bush stunt virus, a gene-silencing suppressor, further enhanced tGFP accumulation by stabilizing mRNA. With this system, tGFP protein was produced at 0.7–1.2 mg/g leaf fresh weight, corresponding to 6.9–12.1% in total soluble protein. These results demonstrate the advantages of rapid and high-level production of recombinant proteins using the geminiviral DNA replicon system for transient expression in plants.